GAMBARAN PENGETAHUAN PASIEN TUBERKULOSIS (TB) PARU TENTANG KEPATUHAN MINUM OBAT DI POLI KLINIK PARU RSUD ARIFIN ACHMAD PROPINSI RIAU - Chairil, -; Azmi, Muhammad (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis is transmitted through the air. The purpose of this study was to determine the Knowledge Overview Patients Tuberculosis (TB) Lung About Drugs in Drinking Compliance Poli Lung Clinic Arifin Achmad Riau Province. The type of research is descriptive with the sampling technique is accidental sampling where the sample in this study are some of the respondents in Lung Clinic Arifin Achmad Hospital Riau province amounted to 45 respondents. Tool data collection using questionnaires and data analysis used is univariate. From the research that has been conducted on 21-25 May 2015 showed that the picture of the knowledge of individuals with tuberculosis (TB) in the lungs majority enough category were 26 respondents (57.8%). Conclusion: Based on the results of these studies are expected in patients with tuberculosis (TB) in the lungs to pay attention to compliance with taking medication so the healing process can be achieved as expected.